New and emerging therapies for acute myeloid leukaemia. (19th August 2018) - Davis, Julian R; Benjamin, David J; Jonas, Brian A
Abstract : The treatment of acute myeloid leukemia (AML) has remained relatively unchanged for the past 3–4 decades with generally poor outcomes, especially in elderly populations unfit for intensive therapy. Recent advancements, however, have identified several cytogenetic and molecular markers that have not only improved prognostication but have also led to the development of several new targeted therapies for specific subpopulations. In 2017, the US Food and Drug Administration approved four new treatments with indications for fms like tyrosine kinase 3 (FLT3)-mutated AML (midostaurin), newly diagnosed or relapsed/refractory CD33+AML (gemtuzumab ozogamicin), newly diagnosed therapy-related AML or AML with myelodysplasia-related changes (CPX-351) and relapsed/refractory AML with an isocitrate dehydrogenase (IDH)2 mutation (enasidenib). These newly approved therapies have demonstrated improved response in their target populations in several pivotal clinical trials with some also demonstrating improved overall survival. Additional novel therapies in development for AML include agents that target B cell lymphoma 2, FLT3, IDH1, the ubiquitination pathway, as well as cell therapy using engineered T cells with chimeric antigen receptors. This review provides a summary of the four newly approved therapies for AML, as well as several promising therapies currently in development.